2007
DOI: 10.1152/ajpendo.00320.2006
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment of the pregnant guinea pig with IGFs promotes placental transport and nutrient partitioning near term

Abstract: Appropriate partitioning of nutrients between the mother and conceptus is a major determinant of pregnancy success, with placental transfer playing a key role. Insulin-like growth factors (IGFs) increase in the maternal circulation during early pregnancy and are predictive of fetal and placental growth. We have previously shown in the guinea pig that increasing maternal IGF abundance in early to midpregnancy enhances fetal growth and viability near term. We now show that this treatment promotes placental trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 82 publications
3
50
0
Order By: Relevance
“…Altered placental differentiation may cause changes in the capacity of the placenta to supply nutrients to the fetus, which continue after treatment and may contribute to changes in fetal and postnatal development following maternal pGH treatment in earlymid pregnancy (Kelley et al 1995, Rehfeldt et al 2001a, Gatford et al 2003. Persistent effects on placental function occur in guinea pigs following maternal infusion with IGF-I from day 20 to 37 of pregnancy (term w67 day), with increased fetal and placental weight at the end of treatment and increased fetal weight, active and passive nutrient transport to the fetus and altered placental gene expression near term (Sferruzzi-Perri et al 2006, 2007a,b, Roberts et al 2008. Expression of IGF axis components were altered in maternal uterine and placental tissues over a month after pGH treatment of early pregnant gilts (days 10-27), although few changes in the axis were observed in placentae collected immediately after treatment (Sterle et al 1998, Freese et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Altered placental differentiation may cause changes in the capacity of the placenta to supply nutrients to the fetus, which continue after treatment and may contribute to changes in fetal and postnatal development following maternal pGH treatment in earlymid pregnancy (Kelley et al 1995, Rehfeldt et al 2001a, Gatford et al 2003. Persistent effects on placental function occur in guinea pigs following maternal infusion with IGF-I from day 20 to 37 of pregnancy (term w67 day), with increased fetal and placental weight at the end of treatment and increased fetal weight, active and passive nutrient transport to the fetus and altered placental gene expression near term (Sferruzzi-Perri et al 2006, 2007a,b, Roberts et al 2008. Expression of IGF axis components were altered in maternal uterine and placental tissues over a month after pGH treatment of early pregnant gilts (days 10-27), although few changes in the axis were observed in placentae collected immediately after treatment (Sterle et al 1998, Freese et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…PGH may also promote lipolysis, because a correlation between PGH and FFA levels was reported at delivery [23] . In guinea pigs, the chronic infusion of IGF-I during the second half of gestation reduces maternal adipose tissue stores, suggesting increased lipolysis which in turn might lead to alterations in the 'nutrient partitioning' between mother and fetus [103,104] .…”
Section: Possible Mechanisms Of Action To Explain Improved Fetal Growthmentioning
confidence: 99%
“…However, the larger placentas in mice with decidual IGFBP-1 overexpression are dysfunctional, resulting in IUGR [60] . The stimulation of placenta growth and maturation, and transplacental nutrient transport appears to be mediated by both locally produced IGF-II [111,112] and circulating IGFs [103,104,113,114] . The guinea pig is an attractive animal model for this type of research, because its hemochorial placenta closely resembles the human placenta; the ovine placenta, however, is substantially different.…”
Section: Possible Mechanisms Of Action To Explain Improved Fetal Growthmentioning
confidence: 99%
“…Although these studies demonstrate that IGF-1 can rescue the phenotype, this was done in early to mid-pregnancy, typically a point in human gestation before diagnosis of late-onset idiopathic IUGR. Similarly, studies by Darp and colleagues 26,27 have demonstrated improved fetal growth after fetal intraamniotic and intravascular delivery of IGF-1 in pregnant sheep; however, multiple weekly injections were required to have an effect. Despite encouraging evidence, these studies also suggest that the use of exogenous protein supplementation of recombinant IGF-1 does not significantly change the primary IUGR end points in a clinically applicable regimen of treatment administration.…”
mentioning
confidence: 95%
“…Human studies also show that growth-restricted fetuses have a reduction in IGF-1, IGF-2, and IGF-binding protein-3 (IGFBP3) and an increase in IGFBP-1. 22,23 Administration of recombinant IGF-1 to the mother has had little success in improving fetal growth in animal models, 24,25 although studies by Sferruzzi-Perri and colleagues 26 did demonstrate an increase in fetal growth and placental nutrient transport in guinea pigs after longterm maternal infusion. Although these studies demonstrate that IGF-1 can rescue the phenotype, this was done in early to mid-pregnancy, typically a point in human gestation before diagnosis of late-onset idiopathic IUGR.…”
mentioning
confidence: 99%